DX Marks the Spot: Linking and Interpreting Artefacts of the former Design Exchange Collection - Windover, Michael; Hadlaw, Jan (Scientia Canadensis, 2024)
This article describes the xDX project: Documenting, Linking, and Interpreting Canada’s Design Heritage. In 2019, the Design Exchange (DX), “Canada’s Design Museum,” deaccessioned its artefact collection and archival fonds to focus instead on public programming. The xDX Project is creating an open-data resource, the xDX ResearchSpace, to preserve the integrity of the former DX collection—now distributed across five institutions—and to support scholarship and public appreciation of modern Canadian design history. The authors propose that xDX’s dispersed artifacts and digital tools continue to facilitate object-oriented research, offering researchers, students, and publics the means to learn about and interrogate Canadian design history.